Investigation the Effect of Cross Linking Agent on Equilibrium Swelling and Kinetics of Water Absorption and Desorption for pH and pH-Temperature Sensitive Hydrogels - KARIMI, ALI (Asian Journal of Chemistry, 2010)
Two type of ionic hydrogel were synthesized. One of these hydrogels is pH sensitive (acrylamide-sodium acrylate copolymer) and other one is pH-temperature sensitive (N-isopropyl acrylamide-sodium acrylate copolymer). They contain different ratios of cross linking agent. The effect of cross linking agent concentration on hydrogel swelling and on amount and kinetics of water sorption and desorption was studied.